Hyaluronic acid in digestive cancers - Wu, Ruolin (Journal of cancer research and clinical oncology, 2017)
PurposeHyaluronan (HA), an extracellular and peri-cellular glycosaminoglycan with a large molecular weight, plays an important role in cancer growth and metastasis. The aim of this study was to summarize the biological roles and regulation of HA and small HA fragments, and their metabolismn enzymes and receptors in human digestive cancers.MethodsA systematic literature search mainly focusing on the biological roles of HA in the development and progression of human digestive cancers was performed using electronic databases.ResultsThe correlation between HA accumulation and tumor progression has been shown in various digestive cancers. HA and HA fragment-tumor cell interaction could activate the downstream signaling pathways, promoting cell proliferation, adhesion, migration and invasion, and inducing angiogenesis, lymphangiogenesis, epithelial-mesenchymal transition, stem cell-like property, and chemoradioresistance in digestive cancers.ConclusionsA better insight into the mechanism of HA and HA fragment involvement in digestive cancer progression might be useful for the development of novel biomarkers and therapeutic strategies.
Published online: 17 August 2016
Gesehen am 18.10.2018